Temperature-fluctuation effects on shrimp protein quality assessed via a multi-stage temperature-fluctuation protein convolutional neural network - Zhexun Yang; Yiling Zhang; Sili Xiao; Weiteng Weng; Ziqi Xie; Jiayi Li; Wen Jie Li; Ying Deng; Yutao Wei; Yudan Li; Shuangyin Liu; Xuekai Gao; et al. (Journal of Food Engineering, 2027)

Flip-Flow bioreactors enhance bioproductions with better oxygen transfer and energy saving - Ge Zhang; Manuel Tianchen Tang; Chao Li; Yongqiang Liu; Wanze Wang; Weike Guo; Xueqing Yi; Yiling Chen; Xuanming Xu; Fuqing Wu; Guo-Qiang Chen (Bioresource Technology, 2026)

​​Integrating machine learning and spatial transcriptomics uncovers shared immunomodulatory deubiquitinases in MAFLD and HCC - Yu-xi Han; Hongze Li; Wendi Xia; Junyi Ma; Jiaqi Zhang; Yiling Li (Human Genetics, 2026)

Overexpression of SiGolS3 enhances cold tolerance in Broussonetia papyrifera by promoting the accumulation of raffinose family oligosaccharides (RFOs) - Zhenhai Zhang; Zhiwei Li; Weixiang Zhou; Boyan Wang; Saisai Wang; Xiaoyan Wu; Qianqin Li; Hongliang Xin; Yiling Liu; Wenwen Xia; Jianbo Zhu (Plant Science, 2026)

Denitrification performance in low C/N water by aerobic denitrifying bacterial consortia coupled with biochar: Effects of pyrolysis temperature and dissolved oxygen - Rui Huo; Yiling Di; Wanying Li; Chenbin Wu; Yingchao Cui; Shilei Zhou (Journal of Environmental Chemical Engineering, 2026)

Sustainable extraction and in situ separation of bromelain from pineapple peel using deep eutectic solvent/salt system: molecular mechanism, hydrolytic activity and stability - Yiling Liu; Qizhen Huang; Yihan Liu; Jiacong Wu; Ming Li; Yun Wang; Juan Han; Lei Wang (Food Research International, 2026)

Effects of carriers and addition modes on the physical and chemical properties of green pepper (Piper nigrum L.) powders treated by freeze-far infrared drying during storage - Xinyi Wang; Yiling Tang; Yue Huang; Hui Su; Xiaoyu Fan; Hongchen Li; Haiming Chen; Ming Zhang; Jianfei Pei; Congfa Li; Wenxue Chen; Ying Lyu (Food Chemistry, 2026)

The impacts of multidimensional urban greenness on incident dyslipidaemia and blood lipid profiles among adults: A 10-year longitudinal cohort study in Hong Kong - Yufei Liu; Siyi Chen; Changqing Lin; Yiling Zheng; Yuanyuan Yi; Jun Yang; Shiu Lun Au Yeung; Jun Ma; Weifeng Li; Tuan Quang Phan; Lingxin Hao; Cui Guo (Environmental Research, 2026)

Millennium-scale dynamics of microbial carbon metabolism genes in coastal soils along a reclamation chronosequence - Min Wang; Yiling Wang; Hanzhu Li; Yuchen Lu; Xinyi Xu; Hang-Wei Hu; Jizheng He; Bin Ma; Xiaofei Lv (CATENA, 2026)

Annual global land cover mapping at 30 m resolution from 1985 to 2022 with high temporal consistency - Bingjie Li; Xiaocong Xu; Haoming Zhuang; Honghui Zhang; Yangzi Che; Yue Zheng; Yiling Cai; Xiaoping Liu; Xia Li (Science Bulletin, 2026)

Modulation of the rhizosphere microbial network by dark septate endophytes enhances salt tolerance in Lycium ruthenicum Murr - Han Li; Meng Zhou; Zhengyu Zhu; Mengmeng Li; Xiaotong Yang; Yiling Zuo; Xueli He (International Biodeterioration & Biodegradation, 2026)

On-site evolution of bifunctional NiCoP nanosheet electrode for electrocatalytic co-produce acetate and hydrogen from ethanol - Nanjia Yang; Yongsheng Wang; Yanan Chen; Yizhen Li; Jiansheng Wang; Chuanyi Zhang; Kaifeng Wang; Yiling Feng; Yuxin Zhu; Wei Zhu; Zhongbin Zhuang (Chemical Engineering Journal, 2026)

Phylogenomics of Rhinogobius gobies reveal northern-southern divergence and trait evolution in China - Suhan Liu; Qinwen Xue; Yun Hu; Jiantao Hu; Yiling Pan; Yun Bu; Jiliang Wang; Jianhong Xia 夏建宏; Chenhong Li 李晨虹 (Molecular Phylogenetics and Evolution, 2026)

Synergistic flavor enhancement and polycyclic aromatic hydrocarbons inhibition in roasted fish by Perilla-clam/yeast composite extracts: Regulation of Maillard reaction and lipid oxidation pathways - Yiling Tian; Tong Li; Yunyue Shan; Shanbai Xiong; Ru Liu; Yueqi An (Food Chemistry, 2026)

Oligomer production and effects on gut microbiota of PLA and PBAT biodegradable microplastics in in vitro digestion model - Guowei Ma; Xiaomeng Gao; Zhihui Li; Yuting Chen; Hanfei Li; Yiling Cui; Peixue Guo; Biao Yang; Di Feng; Tingting Zhao (Food Bioscience, 2026)

Deficiency of primate-specific TFDP3 causes male infertility with oligoasthenoteratozoospermia in humans and cynomolgus monkeys - Chunyu Liu; Chaofeng Tu; Peng Li; Huan Wu; Feng Wan; Yong Lu; Shuyan Tang; Xin Li; Kuokuo Li; Jiaxiong Wang; Yang Gao; Xinyan Geng; et al. (Science China Life Sciences, 2026)

New record of the eightbarbel loach, Lefua costata (Kessler 1876) in Zhejiang, China, with comments on Lefua sayu (Herre and Lin 1936) - Yangkai Shao; Jiantao Hu; Yiling Pan; Chenhong Li (Ichthyological Research, 2026)

2,2’-Biimidazole-based porous organic polymers for efficient capture of radioactive iodine at high temperature and low concentration - Zexing Ma; Chenjie Li; Siying Chen; Chunhui Zhou; Linhai Liu; Yiling Guo; Xiaolong Liu; Wenze Zhang; Song Tu; Jun Li; Xin Yu; Yaqiang Xie (Chemical Engineering Journal, 2026)

Toward a comprehensive map of Rab-mediated cargo transport to migrasomes - Yiling Wen; Yong Li; Jiayi Chen; Dianxing Liu; Yuanchao Li; Ying Li; Haohao Tang; Peizhen Gao; Wenmin Tian; Ning Shen; Yang Chen (Science China Life Sciences, 2026)

A novel method of estimating phytoplankton absorption coefficient for inland waters based on OLCI using Sun-induced chlorophyll-a fluorescence - Wenyu Liu; Yiling Zheng; Jie Lin; Yunmei Li; Honglei Guo; Huaiqing Liu; Yuxin Zhu; Fangfang Chen; Heng Lü; Song Miao (Journal of Oceanology and Limnology, 2026)

Leaching behavior and toxicity of solid waste from ore-based lithium extraction: Implications for safe storage and resource utilization - Jiefeng Liang; Luqian Zheng; Qun Zhang; Jiawen Yang; Bo Lei; Feigang Yuan; Mingyang Li; Wei Jiang; Yiling Li; Xuezhi Yang; Runzeng Liu; Haiyan Zhang; et al. (Water Research, 2026)

Mechanism of flavor enhancement by yeast extract and clam extract in ginger-surimi cake: Insights from flavoromics and machine learning - Yiling Tian; Hanpu Gao; Tong Li; Yunyue Shan; Shanbai Xiong; Ru Liu; Yueqi An (Food Research International, 2026)

Disruption of sphingolipid metabolism triggers lung vascular inflammation and aging-like changes under hypoxia through VDAC1-mediated mitochondrial DNA release - Jin Xu; YiLing Ge; Bin Zhang; SiYuan He; QingLin Cao; PeiJie Li; YingRui Bu; YunGang Bai; Lin Zhang; GuoDong Tan; Jin Ma; ManJiang Xie (Apoptosis, 2026)

Migrion: a Migrasome-mediated unit for intercellular viral transmission - Yuxing Huang; Xiaojie Yan; Xing Liu; Congcong Ji; Wenmin Tian; Haohao Tang; Yong Li; Yiling Wen; Peiyao Fan; Hongli Wang; Cankun Xi; Zhongtian Li; et al. (Science Bulletin, 2026)

High-throughput screening identifies paullinic acid as an antiviral agent against Bombyx mori nucleopolyhedrovirus - Zhenwei Jia; Xiaoli Mo; Shidong Jiang; Li Sui; Yiling Zhang; Xueyang Wang; Jie Cheng; Ping Qian; Xudong Tang (Pesticide Biochemistry and Physiology, 2026)

A novel method for predicting fuel consumption of the LNG dual-fuel ship based on BN-GBM and feature construction - Yiling Lu; Lianzhong Huang; Yanfei Zhang; Jianlin Cao; Haoyang Zhao; Daize Li; Zhang Ruan; Kai Wang; Ranqi Ma (Ocean Engineering, 2026)

Mechanisms, treatment strategies and predictive biomarkers of drug resistance in acute myeloid leukemia - Jianjian Zhuang; Yue Li; Yingqiong Zhang; Yiling Huang; Yijia Han; Nengming Lin; Yangling Li (Mutation Research - Reviews in Mutation Research, 2026)

Hematotoxicity of Fe- and Cr-based metal–organic framework nanoparticles in rockfish Sebastes schlegelii - Yiling Li; Junyu Ye; Meiyu Wang; Yang Gao; Bin Xia; Zhengguo Cui; Keming Qu (Marine Environmental Research, 2026)

ARSGaussian: 3D Gaussian Splatting with LiDAR for aerial remote sensing novel view synthesis - Yiling Yao; Bing Zhang; Wenjuan Zhang; Lianru Gao; Dailiang Peng; Bocheng Li; Yaning Wang; Bowen Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Hybrid calcium carbonate nanoparticles incorporated with capsaicin for tumor therapy via calcium overload mediated mitochondria damage and endoplasmic reticulum stress - Yiling Li; Yiyin Zhang; Guoqiao Chen; Xiaolong Liu; Qiming Xia; Yixuan Li; Jing Yang; Guoqiao Xu; Jiayi Chen; Jun Chen; Guping Tang; Xiaoxiao Fan; et al. (Chemical Engineering Journal, 2026)

Co-variation between bacterial genome traits and root functional traits influences soil multifunctionality of five temperate tree species - Chunhua Lv; Ying Jin; Yiling Li; Zhenghu Zhou (Rhizosphere, 2025)

Constructing a macroporous N-doped carbon hosted ZnO/Fe3O4 composite from Fe-ZIF-8 pyrolysis for highly sensitive detection of carbendazim environmental pollutants - Yaqi Yang; Jiejun Li; Yiling Wang; Zhifang Liu; Caiyu Ge; Yixi Xie; Pengcheng Zhao; Junjie Fei (Journal of Environmental Chemical Engineering, 2025)

Characterization of peptide-enriched walnut meal paste via microbial diversity and metabolite profiling - Wei Chen; Shuo Zhang; Bing Qi; Siting Li; Zhou Chen; Yiling Tian; Aijing Ma; Yingmin Jia (International Journal of Food Microbiology, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Spatiotemporal dependence of heavy precipitation on soil moisture anomalies in the Yangtze River Basin, China - Na Yang; Yiling Yue; Hang Yu; Li Zhang; Jun Yin; Junjie Gao; Yehui Zhang (Science of The Total Environment, 2025)

Waterborne and dietary accumulation and toxicity of iron-based metal-organic framework in cladoceran Moina mongolica Daday - Yiling Li; Zihan Liu; Zhengguo Cui; Keming Qu; Bin Xia (Journal of Hazardous Materials, 2025)

The advantages in crop yields and carbon footprints of maize-soybean relay strip intercropping - Zhidan Fu; Ping Chen; Ping Lin; Yiling Li; Kai Luo; Chao Gao; Tian Pu; Yuze Li; Yushan Wu; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Journal of Environmental Management, 2025)

An approach for mapping phytoplankton communities in freshwater lakes based on phytoplankton absorption features - Yuxin Zhu; Qingxia Miao; Heng Lyu; Yiling Zheng; Wenyu Liu; Yunmei Li; Junda Li; Fangfang Chen; Song Miao (Water Research, 2025)

Efficient nitrogen removal by the aerobic denitrifying bacterium Pseudomonas stutzeri RAS-L11 under triple stresses of high alkalinity, high salinity, and tetracycline: From performance to mechanism - Wanying Li; Rui Huo; Yiling Di; Chun Liu; Shilei Zhou (Bioresource Technology, 2025)

Functionalization-dependent toxicity of MIL-101 metal-organic frameworks to phytoplankton Chlamydomonas reinhardtii - Meiyu Wang; Bin Xia; Zhengguo Cui; Keming Qu; Yiling Li (Aquatic Toxicology, 2025)

Chemical migration, digestive behaviors and effect on gut microbiota of PLA and PBAT oligomers - Guowei Ma; Xiaomeng Gao; Yuting Chen; Hanfei Li; Yiling Cui; Peixue Guo; Tingting Zhao; Feng Di (Journal of Hazardous Materials, 2025)

Response of aerobic denitrification system to long-term stress of sulfamethoxazole, erythromycin and ofloxacin in oligotrophic water - Yiling Di; Wanying Li; Rui Huo; Chenbin Wu; Yuting Zhao; Kun Shi; Shilei Zhou; Chun Liu (Bioresource Technology, 2025)

Curcumin activates the JAK-STAT signaling pathway to enhance the innate immune response against porcine epidemic diarrhea virus infection in vivo and in vitro - Qiancheng Jiang; Xiangyang Liu; Jianbo Yuan; Shujuan Zhang; Yiling Zhang; Zifei Kan; Zheng Niu; Li Zhang; Xia Hu; Yang Zhou; Jing Wang; Fei Li; et al. (Veterinary Microbiology, 2025)

DSE enhances fungal modularity and bacterial connectivity linking rhizospheric responses to licorice growth and drought resistance - Yiling Zuo; Chao He; Xinrong Yang; Wanyun Li; Xueli He (Rhizosphere, 2025)

Structure characterization and biological activity of polysaccharides from Trametes sanguinea (TS-P) and wild Lentinus edodes (LE-P) - Ke Liu; Zheng-ao Sun; Xinlin Li; Xin Qing; Wen Yu; Mengnan Liu; Xiang Ding; Yiling Hou (Food Bioscience, 2025)

Endocrine-disrupting effects of 24 colorants used in food contact materials: In vitro and in silico studies - Guowei Ma; Yiling Cui; Qian Li; Yuting Chen; Peixue Guo; Di Feng; Tingting Zhao (Food and Chemical Toxicology, 2025)

Deep learning MRI-based radiomic models for predicting recurrence in locally advanced nasopharyngeal carcinoma after neoadjuvant chemoradiotherapy: a multi-center study - Chunmiao Hu; Congrui Xu; Jiaxin Chen; Yiling Huang; Qingcheng Meng; Zhian Lin; Xinming Huang; Li Chen (Clinical & Experimental Metastasis, 2025)

Vacuum ultraviolet technologies in environmental purification: Mechanism, influence factor, detoxification effect, reactor design, and application - Chuang Wang; Xiao Li; Renjian Deng; Jinying Du; Xizhen Zhang; Yiling Zhang; Chenglin Liu; Bozhi Ren; Zhiwei Zhao (Chemical Engineering Journal, 2025)

Characterization and performance of efficient heterotrophic nitrification and aerobic denitrification by Comamonas testosteroni HR5 under low temperature and high alkalinity - Rui Huo; Wanying Li; Yiling Di; Shilei Zhou (Journal of Water Process Engineering, 2025)

A 1D spectral approach for efficient modal identification of thin-walled members in shell finite element models - Yiling Dai; Shaokuai Wang; Mingming Xiang; Lingfeng Yin; Zhanjie Li (Engineering Structures, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Homozygous deleterious variants in MYCBPAP induce asthenoteratozoospermia involving abnormal acrosome biogenesis, manchette structure and sperm tail assembly in humans and mice - Yiling Zhou; Chaofeng Tu; Charles Coutton; Jianan Tang; Shixiong Tian; Shuyan Tang; Guillaume Martinez; Dapeng Zhou; Célia Tebbakh; Jiaxiong Wang; Raoudha Zouari; Xuehai Zhou; et al. (Science China Life Sciences, 2025)

HTBPPS: A high-throughput behavioral phenotyping platform for shrimp - Wenzhi Cheng; Huimin Peng; Chuanxi Chen; Heqian Zhang; Yiming Wei; Jinqian Yang; Xiaojie Deng; Yiling Hou; Siqi Li; Tingting Huang; Yougen Chen; Chichi Liu; et al. (Aquaculture, 2025)

The denitrification mechanism and microbial responses of oligotrophic aerobic denitrifying bacteria coupled with various sources biochar - Yiling Di; Rui Huo; Wanying Li; Chenbin Wu; Shilei Zhou (Journal of Water Process Engineering, 2025)

Response mechanism of bacterial community and physicochemical factors evolution to ecological restoration in sediment and water dual medium of Baiyangdian Lake - Yuting Zhao; Wanying Li; Rui Huo; Chenbin Wu; Yiling Di; Kun Shi; Shilei Zhou (Journal of Water Process Engineering, 2025)

Study on induced flow patterns and inlet velocity in inclined tunnel fire with natural ventilation - Xiaofeng Chen; Jiangdong Li; Yiling Ni; Zhirong Liang; Hangqiang Ding; Lei Liu; Xin Zhang; Ke Wu; Tianhang Zhang (Tunnelling and Underground Space Technology, 2025)

Exploring collective activity space and its spatial heterogeneity using mobile phone signaling Data: A case of Shenzhen, China - Juan Li; Pengjun Zhao; Mengzhu Zhang; Yiling Deng; Qiyang Liu; Yanzhe Cui; Zhaoya Gong; Juan Liu; Wenchang Tan (Travel Behaviour and Society, 2025)

Rescaled range/vector autoregressive-based changing characteristics of dry season streamflow in the Yujiang River Basin, Southern China - Xu Dong; Xungui Li; Yiling Liu (Stochastic Environmental Research and Risk Assessment, 2025)

DNAzyme assisted single amplification for FEN1 activity detection using a personal glucose meter - Mingxi Li; Weijie Zang; Shuiliang Wang; Zhannuo Lin; Shu Liu; Yiling Chen; Xiaohui Ruan; Yuanfang Luo; Chao Xing; Chunhua Lu (Analytica Chimica Acta, 2025)

Impact of dietary protein and lipid levels and growth rates on the intestinal microbiota of kuruma shrimp (Penaeus japonicus) - Chuanxi Chen; Chunxiang Ai; Wenzhi Cheng; Huiyang Huang; Guangjie Fang; Yiling Hou; Xiaojie Deng; Siqi Li; Tingting Huang; Yougen Chen; Peng Xu; Yong Mao (Aquaculture International, 2025)

The intestinal-hepatic axis: a comprehensive review on fructose metabolism and its association with mortality and chronic metabolic diseases - Yiling Dong; Wen Li; Jun Yin (Critical Reviews in Food Science and Nutrition, 2024)

Disruption of network hierarchy pattern in bulimia nervosa reveals brain information integration disorder - Yiling Wang; Lirong Tang; Jiani Wang; Weihua Li; Miao Wang; Qian Chen; Zhenghan Yang; Zhanjiang Li; Zhenchang Wang; Guowei Wu; Peng Zhang (Appetite, 2024)

Efficient activation of peracetic acid by defect-engineered MoO2−x: Oxygen vacancies and surface Mo(Ⅴ)-mediated electron transfer processes - Jinpeng Wang; Boran Wang; Yubiao Li; Yiling Yang; Caiyan Gao; Xiaoyong Wu (Journal of Hazardous Materials, 2024)

Population genetic analyses of Eastern Chinese Han nationality using ForenSeq™ DNA Signature Prep Kit - Ruiyang Tao; Xinyu Dong; Xiaoyuan Zhen; Ruocheng Xia; Yiling Qu; Shiquan Liu; Suhua Zhang; Chengtao Li (Molecular Genetics and Genomics, 2024)

Seasonal variation of antioxidant bioactive compounds in southern highbush blueberry leaves and non-destructive quality prediction in situ by a portable near-infrared spectrometer - Jianbo Qi; Shuai Sun; Liuqiang Zhang; Yilin Zhu; Huiji Zhou; Xiaona Gan; Bo Li; Yiling Chen; Wei Li; Tingzhao Li; Yiming Li; Gangqiang Dong; et al. (Food Chemistry, 2024)

Enhanced removal of phenolic pollutants over MnO2 initiated by peracetic acid: In situ generation of a heterogeneous Mn(III)-hydroperoxo complex - Xueyan Liu; Kangping Cui; Yiling Yao; Xing Chen; Chen-Xuan Li; Yihan Chen; Zhenhu Hu; Minshu Cui (Chemical Engineering Journal, 2024)

GMPR2-MDA5 interaction bridged the cell junction and anti-GCRV immune - Mingxue Sun; Yiling Li; Hao Tang; Wei Duan; Yijing Liao; Tiaoyi Xiao; Yaoguo Li (Aquaculture, 2024)

P-phenylenediamine antioxidants and their quinone derivatives: A review of their environmental occurrence, accessibility, potential toxicity, and human exposure - Yuting Liang; Feng Zhu; Jie Li; Xin Wan; Yiling Ge; Geyu Liang; Yonglin Zhou (Science of The Total Environment, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Non-radical activation of persulfate with Bi2O3/BiO1.3I0.4 for efficient degradation of propranolol under visible light - Yuehua Deng; Qianqian Che; Yani Li; Jiating Luo; Xiang Gao; Yan He; Yiling Liu; Tong Liu; Xiaolong Zhao; Xiaobin Hu; Wei Zhao (Journal of Environmental Sciences, 2024)

LC–MS and MALDI–MSI-based metabolomic approaches provide insights into the spatial–temporal metabolite profiles of Tartary buckwheat achene development - Tingxia Liu; Peng Wang; Yiling Chen; Boshi Sun; Qing Li; Huihua Wan; Wei Yang; Pengda Ma; Dong Zhang; Gangqiang Dong; Shilin Chen; Qingfu Chen; et al. (Food Chemistry, 2024)

Rapid fluorescent nucleic acid sensing with ultra-thin gold nanosheets - Peiyin Li; Huiyang Zhang; Zhenyu Yang; Yiling Li; Manli Huang; Lingzhi Yang; Xueji Zhang (Analytica Chimica Acta, 2024)

Zinc-associated phospholipid metabolic alterations and their impacts on ALT levels in workers - Yuanyuan Wang; Yiling Li; Qiying Nong; Guohuan Zhang; Nian Liu; Hua Guo; Qinghao He; Lihong Liu; Guangbo Qu; Bin He; Ligang Hu; Guibin Jiang (Science of The Total Environment, 2024)

Phthalate acid esters: A review of aquatic environmental occurrence and their interactions with plants - Jiefeng Liang; Xiaomeng Ji; Xiaoxia Feng; Pinjie Su; Wenzhuo Xu; Qingzhe Zhang; Zhihua Ren; Yiling Li; Qingqing Zhu; Guangbo Qu; Runzeng Liu (Journal of Hazardous Materials, 2024)

Microcystis-dominated paddy crusts enhancing the cadmium accumulation in rice plant (Oryza sativa L.) - Xiaolin Kuang; Zhixuan Wang; Liang Peng; Yuanlong Wang; Huijuan Song; Changwu Li; Ke Song; Yiling Hu (International Biodeterioration & Biodegradation, 2024)

Toxic effects and action mechanism of metal-organic framework UiO-66-NH2 in Microcystis aeruginosa - Yiling Li; Wen-Xiong Wang (Environmental Pollution, 2024)

LDH nanocrystal@amorphousness core–shell structure derived from LDH → LDO transformation: Synergistically enhanced energy stored for LIBs anode - Kai Yang; Yiling Huang; Peixing Wang; Yixuan Tang; Yiwen Zhu; Xiaoxue Zhu; Yan Xu; Wei Jiang; Limei Pan; Qian Li; Haijiao Xie; Jian Yang (Chemical Engineering Journal, 2024)

Application of biological soil crusts for efficient cadmium removal from acidic mine wastewater - Xiaolin Kuang; Yiling Hu; Liang Peng; Dan Li; Huijuan Song; Ke Song; Changwu Li; Yuanlong Wang; Shilong He (Journal of Hazardous Materials, 2024)

Enhanced nitrate removal efficiency and microbial response of immobilized mixed aerobic denitrifying bacteria through biochar coupled with inorganic electron donors in oligotrophic water - Jiajing Meng; Yiling Di; Yuting Geng; Wanying Li; Rui Huo; Shilei Zhou (Bioresource Technology, 2024)

Distribution characteristics and migration trends of hexabromocyclododecanes between seawater-sediment system in different seasons of fishing grounds along the Yellow sea and East China sea coasts - Ke Ning; Aifeng Liu; Minggang Zheng; Yiling Li; Shanmin Hu; Ling Wang (Marine Environmental Research, 2024)

Photocatalytic activation of oxalic acid over FeOOH loaded FeWO4/WO3 heterojunction for high-efficient degradation of tetracycline - Qingqing Chai; Jiahan Dong; Xiaofang Yu; Xiaoke Zhang; Jun Li; Sheng Guo; Yiling Yang (Journal of Environmental Chemical Engineering, 2024)

Bufogarlides A-C, three new bufadienolides with Δ 14,15 double bond from the skins of Bufo bufo gargarizans - Lingjie Meng; Qinghong Kong; Jianxun Xie; Feng Pan; Keyu Lu; Sanhua Li; Yiling Li; Di Zhang; Yun Liu (Natural Product Research, 2024)

Genetic diversity, genetic differentiation and demographic history of Cryptomeria (Cupressaceae), a tertiary relict plant in East Asia based on RAD sequencing - Xinyu Li; Mengying Cai; Minqiu Wang; Xingtong Wu; Saneyoshi Ueno; Kentaro Uchiyama; Yunosuke Onuma; Minjun Dai; Yiling Tao; Yafeng Wen; Yoshihiko Tsumura (European Journal of Forest Research, 2024)

Cuprotosis clusters predict prognosis and immunotherapy response in low-grade glioma - Wenjun Zhu; Ziqi Chen; Min Fu; Qianxia Li; Xin Chen; Xiaoyu Li; Na Luo; Wenhua Tang; Feng Yang; Yiling Zhang; Yuanyuan Zhang; Xiaohong Peng; et al. (Apoptosis, 2024)
Cuprotosis, an emerging mode of cell death, has recently caught the attention of researchers worldwide. However, its impact on low-grade glioma (LGG) patients has not been fully explored. To gain a deeper insight into the relationship between cuprotosis and LGG patients’ prognosis, we conducted this study in which LGG patients were divided into two clusters based on the expression of 18 cuprotosis-related genes. We found that LGG patients in cluster A had better prognosis than those in cluster B. The two clusters also differed in terms of immune cell infiltration and biological functions. Moreover, we identified differentially expressed genes (DEGs) between the two clusters and developed a cuprotosis-related prognostic signature through the least absolute shrinkage and selection operator (LASSO) analysis in the TCGA training cohort. This signature divided LGG patients into high- and low-risk groups, with the high-risk group having significantly shorter overall survival (OS) time than the low-risk group. Its predictive reliability for prognosis in LGG patients was confirmed by the TCGA internal validation cohort, CGGA325 cohort and CGGA693 cohort. Additionally, a nomogram was used to predict the 1-, 3-, and 5-year OS rates of each patient. The analysis of immune checkpoints and tumor mutation burden (TMB) has revealed that individuals belonging to high-risk groups have a greater chance of benefiting from immunotherapy. Functional experiments confirmed that interfering with the signature gene TNFRSF11B inhibited LGG cell proliferation and migration. Overall, this study shed light on the importance of cuprotosis in LGG patient prognosis. The cuprotosis-related prognostic signature is a reliable predictor for patient outcomes and immunotherapeutic response and can help to develop new therapies for LGG.

DNA hypomethylation-associated transcriptional rewiring enables resistance to heavy metal mercury (Hg) stress in rice - Weixuan Cong; Ning Li; Yiling Miao; Yuxi Huang; Wenhao Zhao; Ying Kang; Bingqi Zhang; Jinbin Wang; Jiayu Zhang; Yinhe Lv; Jiamo Li; Jian Zhang; et al. (Journal of Hazardous Materials, 2024)

Occurrence and bioaccumulation of parabens and their metabolites in the biota from a subtropical freshwater river ecosystem: Implications for human exposure - Yiling Lin; Yanan Zhao; Yuxian Liu; Yongyin Lan; Jiamin Zhu; Yanpeng Cai; Fen Guo; Feilong Li; Yuan Zhang; Zhihao Xu; Jingchuan Xue (Environmental Research, 2024)

Chiral Au nanostars for SERS sensing of enantiomers discrimination, multibacteria recognition and photothermal antibacterial application - Xueqin Huang; Qiuxia Chen; Yiling Ma; Chan Huang; Weixia Zhi; Jiahao Li; Runmin Zeng; Jiang Pi; Jun-fa Xu; Jun Xu; Wanyong Yang; Jianglin Zhang; et al. (Chemical Engineering Journal, 2024)

Biodegradable cellulose/curcumin films with Janus structure for food packaging and freshness monitoring - Weiquan Wang; Xuewen Liu; Fan Guo; Yuxuan Yu; Jinqing Lu; Yiling Li; Qiaoyun Cheng; Jinping Peng; Goubin Yu (Carbohydrate Polymers, 2024)

Research advances of molecular docking and molecular dynamic simulation in recognizing interaction between muscle proteins and exogenous additives - Genpeng Bai; Yiling Pan; Yuemei Zhang; Yang Li; Jinpeng Wang; Ying Wang; Wendi Teng; Guofeng Jin; Fang Geng; Jinxuan Cao (Food Chemistry, 2023)

Identification of lead-binding proteins as carriers and potential molecular targets associated with systolic blood pressure - Qiying Nong; Baowei Chen; Yongshun Huang; Yiling Li; Yuanyuan Wang; Lihong Liu; Bin He; Tiangang Luan; Ligang Hu; Guibin Jiang (Chemosphere, 2023)

An operational approach for large-scale mapping of water clarity levels in inland lakes using landsat images based on optical classification - Shijiao Lu; Yingchun Bian; Fangfang Chen; Jie Lin; Heng Lyu; Yunmei Li; Huaiqing Liu; Yang Zhao; Yiling Zheng; Linze Lyu (Environmental Research, 2023)

Campus relocation as a natural experiment to investigate the determinants of commuting satisfaction - Yiling Deng; Weini Li; Mengwei Chen (Travel Behaviour and Society, 2023)

Coordination among root exudation C, mycorrhizal colonization, and functional traits and their responses to drought in five temperate tree species - Chunhua Lv; Chuankuan Wang; Yiling Li; Zhenghu Zhou (Forest Ecology and Management, 2023)

Effect of pH treatment on physical stability and antioxidant activity of buckwheat protein/soybean polysaccharide nanocomplex embedded pterostilbene - Dongze Li; Ling Zhu; Qiming Wu; Yiling Chen; Gangcheng Wu; Hui Zhang (Food Bioscience, 2023)

Analysis on multi period activity and evolution of Yingxiu-Beichuan fault in Longmenshan area - Ding Xiao; Li Zhongquan; Li Dian; Hu Yiling; Long Wei; Li Jianing; Liu Henglin (Ore and Energy Resource Geology, 2023)

Different interactions between Tartary buckwheat protein and Tartary buckwheat phenols during extraction: Alterations in the conformation and antioxidant activity of protein - Dongze Li; Ling Zhu; Qiming Wu; Yiling Chen; Gangcheng Wu; Hui Zhang (Food Chemistry, 2023)

Effects of enzyme deactivation conditions on the structure, bound phenol content and antioxidant property of phenol modified Tartary buckwheat protein hydrolysate - Dongze Li; Ling Zhu; Qiming Wu; Yiling Chen; Gangcheng Wu; Hui Zhang (Food Bioscience, 2023)

Structures, issues, and optimization strategies of Ni-rich and Co-low cathode materials for lithium-ion battery - Honggui Xie; Huarong Peng; Dongting Jiang; Zhe Xiao; Xueping Liu; Hao Liang; Mingli Wu; Dongming Liu; Yun Li; Yiling Sun; Shengkui Zhong; Zhengfang Qian; et al. (Chemical Engineering Journal, 2023)

Effects of dietary adenosine and adenosine 5′-monophosphate supplementation on carcass characteristics, meat quality, and lipid metabolism in adipose tissues of finishing pigs - Sujuan Rao; Zhijuan Cui; Longmiao Zhang; Shuo Ma; Shuangbo Huang; Li Feng; Yiling Chen; Jinxi Luo; Jinfeng Li; Shiyu Qian; Hanting Liu; Yanzhi Liu; et al. (Meat Science, 2023)

Bone marrow mesenchymal stem cell-derived exosomes loaded with miR-26a through the novel immunomodulatory peptide DP7-C can promote osteogenesis - Shuang Lai; Li Deng; Cong Liu; Xinlun Li; Liyuan Fan; Yushu Zhu; Yiling Yang; Yandong Mu (Biotechnology Letters, 2023)

Global, region and national trends and age-period-cohort effects in colorectal cancer burden from 1990 to 2019, with predictions to 2039 - Shuhua Hu; Yiling Li; Wenmin Zhu; Jialin Liu; Sheng Wei (Environmental Science and Pollution Research, 2023)

Oxidation treatment of shale gas produced water: Molecular changes in dissolved organic matter composition and toxicity evaluation - Yiling Zhuang; Yufei Ji; Qiyue Kuang; Zhaoji Zhang; Peng Li; Junbei Song; Niqian He (Journal of Hazardous Materials, 2023)

Fatal landslides in China from 1940 to 2020: occurrences and vulnerabilities - Shuai Zhang; Can Li; Jingyu Peng; Yiling Zhou; Shuairong Wang; Yunmin Chen; Yao Tang (Landslides, 2023)

Ecological drivers and potential functions of viral communities in flooded arsenic-contaminated paddy soils - Ruichuan Gao; Bin Ma; Min Hu; Liping Fang; Guanhong Chen; Wenqiang Zhang; Yiling Wang; Xinwei Song; Fangbai Li (Science of The Total Environment, 2023)

Mineralization and electroreduction-recycling of toxic Pb2+ ions using memory-effect of layered double hydroxide structure with ultrahigh capacity - Changjuan Li; Zixian Li; Jikang Wang; Wenbo Xiong; Hong Yan; Yiling Bai; Dermot O'Hare; Yufei Zhao (Chemical Engineering Journal, 2023)

Identifying the hygroscopic properties of fine aerosol particles from diverse sources in urban atmosphere and the applicability in prediction of cloud nuclei - Jingye Ren; Fang Zhang; Lu Chen; Gang Cao; Mengyu Liu; Xue Li; Hao Wu; Yiling Cheng; Zhanqing Li (Atmospheric Environment, 2023)

Elucidation of the GAUT gene family in eight Rosaceae species and function analysis of PbrGAUT22 in pear pollen tube growth - Yiling Cai; Chao Tang; Shouzheng Lv; Qiming Chen; Xiaoxuan Zhu; Xian Li; Kaijie Qi; Zhihua Xie; Shaoling Zhang; Peng Wang; Juyou Wu (Planta, 2023)

Changes in soil fungal community composition and functional groups during the succession of Alpine grassland - Wen Zhao; Yali Yin; Shixiong Li; Yiling Dong; Shifeng Su (Plant and Soil, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

A chromosome‐level Populus qiongdaoensis genome assembly provides insights into tropical adaptation and a cryptic turnover of sex determination - Yiling Li; Deyan Wang; Weiwei Wang; Wenlu Yang; Jinwen Gao; Wenyan Zhang; Lanxing Shan; Minghui Kang; Yang Chen; Tao Ma (Molecular Ecology, 2023)
Populus species have long been used as model organisms to study the adaptability of trees and the evolution of sex chromosomes. As a species belonging to the section Populus and limited to tropical areas, the P. qiongdaoensis genome contains important information for tropical poplar studies and protection. Here, we report a chromosome‐level genome assembly and annotation of a female P. qiongdaoensis . Gene family clustering, positive selection detection and historical reconstruction of population dynamics revealed the tropical adaptation of P. qiongdaoensis , and showed convergent evolution with another tropical poplar, P. ilicifolia , at the molecular level, especially on some functional genes (e.g., PIF3 and PIL1 ). In addition, we also identified a ZW sex determination system on chromosome 19 of P. qiongdaoensis , and inferred that it seems to have a similar sex determination mechanism to other poplars, controlled by a type‐A cytokinin response regulator ( RR ) gene. However, comparison and phylogenetic analysis of the sex determination regions confirmed a cryptic sex turnover event in the section Populus , which may be caused by the translocation and duplication of the RR gene driven by Helitron ‐like transposable elements. Our study provides new insights into the environmental adaptation and sex chromosome evolution of poplars, and emphasizes the importance of using long read sequencing in ecological and evolutionary inferences of plants.

The capability of chloramphenicol biotransformation of Klebsiella sp. YB1 under cadmium stress and its genome analysis - Zewen Tan; Xiuyue Yang; Yiling Liu; Lian Chen; Huijuan Xu; Yongtao Li; Beini Gong (Chemosphere, 2023)

Pollution mechanisms and photochemical effects of atmospheric HCHO in a coastal city of southeast China - Taotao Liu; Yiling Lin; Jinsheng Chen; Gaojie Chen; Chen Yang; Lingling Xu; Mengren Li; Xiaolong Fan; Fuwang Zhang; Youwei Hong (Science of The Total Environment, 2023)

Geographic distribution pattern and ecological niche differentiation of endangered Opisthopappus in Taihang Mountains - Li Liu; Hao Zhang; En Zang; Qiyang Qie; Shan He; Weili Hao; Yafei Lan; Zhixia Liu; Genlou Sun; Yiling Wang (Brazilian Journal of Botany, 2023)

Effects of furanic compounds from biomass pyrolysis on ketonization reaction: The role of oxygenated side groups - Wenran Gao; Yiling Wan; Shanhui Zhao; Muhammad Asif Akhtar; Kuan Ding; Bin Li; Yinlong Wu; Shoujun Zhang; Shu Zhang (Fuel, 2023)

Isolation and identification of two Beauveria bassiana strains from silkworm, Bombyx mori - Yiling Zhang; Xu Yang; Jiao Zhang; Mingzhen Ma; Ping He; Yu Li; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2022)

Knockdown of SOX9 alleviates tracheal fibrosis through the Wnt/β-catenin signaling pathway - Lei Gu; Anmao Li; Jing Lin; Yiling Gan; Chunyan He; Rui Xiao; Jiaxin Liao; Yishi Li; Shuliang Guo (Journal of Molecular Medicine, 2022)

Spatial–temporal variations and pollution risks of mercury in water and sediments of urban lakes in Guangzhou City, South China - Xiaojun Wang; Wei Zhong; Bingxiang Wang; Mingying Quan; Tianhang Li; Durui Lin; Shengtan Shang; Chan Zhu; Churan Zhang; Yiling Liao (Environmental Science and Pollution Research, 2022)

Source variation and tempo-spatial characteristics of health risks of heavy metals in surface dust in Beijing, China - Leiping Cao; Ruimin Liu; Yiling Zhou; Cong Men; Lin Li (Stochastic Environmental Research and Risk Assessment, 2022)

Risk assessment of rare earth elements in fruits and vegetables from mining areas in China - Ziwei Shi; Ling Yong; Zhaoping Liu; Yibaina Wang; Haixia Sui; Weifeng Mao; Lei Zhang; Yiling Li; Jialin Liu; Sheng Wei; Yan Song (Environmental Science and Pollution Research, 2022)

Genome-wide locus-specific DNA methylation repatterning may facilitate rapid evolution of mercury resistance in rice - Weixuan Cong; Ning Li; Jinbin Wang; Ying Kang; Yiling Miao; Chunming Xu; Ziqi Wang; Tongtong Liu; Lei Gong; Bao Liu; Xiufang Ou (Genes & Genomics, 2022)

Growth-promoting effects of dark septate endophytes on the non-mycorrhizal plant Isatis indigotica under different water conditions - Min Li; Lifeng Hou; Jiaqiang Liu; Jingya Yang; Yiling Zuo; Lili Zhao; Xueli He (Symbiosis, 2021)

The Amygdala Responds Rapidly to Flashes Linked to Direct Retinal Innervation: A Flash-evoked Potential Study Across Cortical and Subcortical Visual Pathways - Yanmei Chen; Yiling Ni; Jianhong Zhou; Hua Zhou; Qian Zhong; Xinyue Li; Jichuan Zhang; Yuanye Ma; Jingkuan Wei (Neuroscience Bulletin, 2021)

Colonization by dark septate endophytes improves the growth of Hedysarum scoparium under multiple inoculum levels - Yiling Zuo; Fang Su; Xueli He; Min Li (Symbiosis, 2020)

Isolation and identification of two Serratia marcescens strains from silkworm, Bombyx mori - Yiling Zhang; Ruisha Shang; Jiao Zhang; Junhao Li; Guanyu Zhu; Mingshuai Yao; Jiancheng Sun; Zhongyuan Shen (Antonie van Leeuwenhoek, 2020)

Olfaction is a Marker of Severity but Not Diagnosis in Anorexia Nervosa: a Systematic Review and Meta-Analysis - Yiling Mai; Xin Zhang; Zetian Li; Xiaohua Wu; Baoer Zeng; Yuan Fang; Laiquan Zou; Jiubo Zhao; Thomas Hummel (Neuropsychology Review, 2020)

Mesoscopic Crack Initiation, Propagation, and Coalescence Mechanisms of Coal Under Shear Loading - Lichao Cheng; Jiang Xu; Shoujian Peng; Yixin Liu; Gang Chen; Xinwang Li; Yiling Qin (Rock Mechanics and Rock Engineering, 2019)

Reduction of Pb availability during surficial leaching in different types of soils with addition of apatite and oxalic acid - Chenmeng Guo; Weitao Tian; Zhijun Wang; Feiyu Han; Mu Su; Yiling Wu; Zhen Li; Shuijin Hu (Journal of Soils and Sediments, 2019)

Preventive effect on endothelial surface layer damage of Fusu agent in LPS-induced acute lung injury in rats - Peiyang Gao; Chengshi He; Chuantao Zhang; Baixue Li; Yiling Guo; Wen Zhao; Quan Xie; Xuemei Zhang (Molecular and Cellular Biochemistry, 2019)

Immunization with an adenovirus-vectored TB vaccine containing Ag85A-Mtb32 effectively alleviates allergic asthma - Yiling Zhang; Ying Feng; Liang Li; Xianmiao Ye; Jinlin Wang; Qian Wang; Pingchao Li; Na Li; Xuehua Zheng; Xiang Gao; Chufang Li; Feng Li; et al. (Journal of Molecular Medicine, 2018)

In vivo gene expression profiling of the entomopathogenic fungus Beauveria bassiana elucidates its infection stratagems in Anopheles mosquito - Yiling Lai; Huan Chen; Ge Wei; Guandong Wang; Fang Li; Sibao Wang (Science China Life Sciences, 2017)

Overexpression, purification, molecular characterization and the effect on tumor growth of ribosomal protein L22 from the Giant Panda (Ailuropoda melanoleuca) - Jian Li; Yiling Hou; Xiang Ding; Wanru Hou; Bo Song; Yichun Zeng (Molecular Biology Reports, 2014)

Trap Induction and Trapping in Eight Nematode-trapping Fungi (Orbiliaceae) as Affected by Juvenile Stage of Caenorhabditis elegans - Hongyan Xie; F. M. Aminuzzaman; Lingling Xu; Yiling Lai; Feng Li; Xingzhong Liu (Mycopathologia, 2010)

Molecular characterization and association analysis of porcine PANE1 gene - Honggang Huang; Hong Deng; Yiling Yang; Zhonglin Tang; Shulin Yang; Yulian Mu; Wentao Cui; Jing Yuan; Zhenfang Wu; Kui Li (Molecular Biology Reports, 2010)

Isolation and characterization of a novel cDNA encoding methyl jasmonate-responsive transcription factor TcAP2 from Taxus cuspidata - Yiling Dai; Qiulin Qin; Dalin Dai; Lisheng Kong; Wei Li; Xiaojun Zha; Yuanjie Jin; Kexuan Tang (Biotechnology Letters, 2009)

KRC transcripts: identification of an unusual alternative splicing event - Chi-Ho Mak; Ziling Li; Carl Eugene Allen; Yiling Liu; L.-C. Wu (Immunogenetics, 1998)